2022
DOI: 10.1038/s41598-022-23794-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic differences and implications on treatment strategies between butterfly glioblastoma and glioblastoma with unilateral corpus callosum infiltration

Abstract: Approximately 25% of glioblastomas show at diagnosis a corpus callosum infiltration, which is associated with poor prognosis. The extent of corpus callosum involvement, however, ranges from partial unilateral to complete bilateral infiltration. The role of surgery in glioblastoma with corpus callosum involvement is controversial. In this study, we aimed to examine prognostic differences between glioblastoma with unilateral and glioblastoma with bilateral corpus callosum infiltration, and to evaluate possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Interestingly, Wang et al ( 2018 ) showed that patients with H3K27M-mutant gliomas in unusual anatomical locations (cerebellum, corpus callosum, lateral ventricle, frontal, and temporal lobe) had a better prognosis compared with those with corresponding tumors in the brainstem. Recently, Hazaymeh et al ( 2022 ) showed that patients affected by glioblastoma multiforme (GBM) undergoing gross total resection exhibited a significant survival benefit compared to their counterparts without gross total resection. Our cases 1 and 2 developed osseous metastases 5 months and 6 months, respectively, since the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al ( 2018 ) showed that patients with H3K27M-mutant gliomas in unusual anatomical locations (cerebellum, corpus callosum, lateral ventricle, frontal, and temporal lobe) had a better prognosis compared with those with corresponding tumors in the brainstem. Recently, Hazaymeh et al ( 2022 ) showed that patients affected by glioblastoma multiforme (GBM) undergoing gross total resection exhibited a significant survival benefit compared to their counterparts without gross total resection. Our cases 1 and 2 developed osseous metastases 5 months and 6 months, respectively, since the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by rapid growth and high invasiveness, this devastating disease has a dismal prognosis, with a median survival of approximately 15-18 months post-diagnosis even with treatment [2]. This is primarily attributed to the infiltrative behavior and localization of the tumor, as well as, to the extent of surgery and treatment resistance [3][4][5]. The established treatment protocol for GB patients involves surgical resection followed by cycles of chemoradiotherapy and adjuvant chemotherapy (temozolomide-TMZ) [6,7].…”
Section: Introductionmentioning
confidence: 99%